2022
DOI: 10.3390/ani12192531
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Radiographic Measurements of Heart and Left Atrial Size in Dogs with and without Myxomatous Mitral Valve Disease: Intra- and Interobserver Agreement and Practicability of Different Methods

Abstract: Dogs suffering from Myxomatous Mitral Valve Disease (MMVD) show a potential heart enlargement, especially in the left atrium, detectable by radiography. Due to digital radiography, different radiographic measurements estimate cardiac size quite uncomplicatedly. The Vertebral Heart Size (VHS), Radiographic Left Atrial Dimension (RLAD), Left Atrial Width (LAWidth), and the Vertebral Left Atrial Size (VLAS) used anatomical landmarks for measuring cardiac size in relation to the vertebral column. This study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
2
4
1
Order By: Relevance
“…Interobserver agreement for the 23 dogs compared was better for the VHS than the TIHS, 0.87 and 0.78, respectively. The interobserver agreement in the VHS for the MMVD dogs, 0.85, was lower compared to previous studies with MMVD dogs, ranging between 0.96 [ 51 ] and 0.92 [ 52 ]. The agreement between observers in the TIHS for the control group was 0.77.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Interobserver agreement for the 23 dogs compared was better for the VHS than the TIHS, 0.87 and 0.78, respectively. The interobserver agreement in the VHS for the MMVD dogs, 0.85, was lower compared to previous studies with MMVD dogs, ranging between 0.96 [ 51 ] and 0.92 [ 52 ]. The agreement between observers in the TIHS for the control group was 0.77.…”
Section: Discussioncontrasting
confidence: 78%
“…The TIHS method being a ratio can change with a small difference in some of the magnitudes that take part in its calculation when measured by different observers. Previous studies have concluded that the VHS was independent of the observer’s experience [ 51 , 52 ] but dependent of individual observer. This could be the case for the TIHS too, as it is an adaptation of the VHS method.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple previous studies have demonstrated that measurement variability of VHS, VLAS, or both are relatively stable when comparing different investigators. 2,4,6,18,35,36 In conclusion, when echocardiography is unavailable, VLAS and murmur grade have clinical utility to aid in differentiating cardiogenic from noncardiogenic causes of respiratory signs, whereas VHS might be less useful. These results might be especially useful to help rule out CHF in dogs with respiratory signs and increased VHS.…”
Section: Discussionmentioning
confidence: 98%
“…However, this approach could limit the external validity of our results, because a single trained investigator does not represent all individuals (with variable levels of expertise and experience) performing radiographic measurements for clinical purposes. Multiple previous studies have demonstrated that measurement variability of VHS, VLAS, or both are relatively stable when comparing different investigators 2,4,6,18,35,36 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the finding of this study should be interpreted in regard to this limitation. Lastly, we did not include an inter‐ and intraobserver analysis; however, these two radiographic measurements have already proven effective, generating low variability among different observers 29 …”
Section: Discussionmentioning
confidence: 99%